Abstinência de nicotina altera as bandas nas oscilações de baixa frequência no eletrocorticograma de ratos Wistar - LIMA, Danielma Carvalho de (2023)
Introduction: Nicotine is a psychostimulant present in tobacco. After being inhaled, a substance attains knowledge in a few seconds. Previous studies that can be used to describe the effects of the screen (delta, tenicotine, alpha, describe and gamma) However, there are drugs to the drug profile during periods of withdrawal. Objectives: Characterize as electrophysiological does not show changes in animals in nicotine withdrawal. Methodology: Thirty-six adult Wistar rats were used, divided into the following groups: a) Control group (n=9); b) Nicotine group (group treated with 1mg/kg nicotine via i.p.) (n=9); c) Group treated with nicotine (1 mg/ml) at a dose of 1 mg/kg i.p. for 14 days, with abstinence for 24 hours (n=9); d) Group treated with nicotine (1 mg/ml) at a dose of 1 mg/kg i.p. for 14 days with abstinence of 48 hours (n=9). Electroencephalic studies were performed to assess the graphic wave profile in each group. Results: The group of previously sensitized rats that received nicotine in a definite way and a greater increase in the amplitude of all waves found in studies were never increased, differing from the results found in studies in studies. In the abstinent groups, there was an increase in the power of delta waves, and a reduction in theta, alpha, beta and gamma waves. Conclusion: As electrocorticographic changes corroborate the theory that the acute effects of withdrawal may be related to electromagnetic waves. The profile described of the associates during 24 and 48 hours of abstinence is in fact the series of the cognitive, mental, physical and social performance. The description of changes implemented in this electrophysiological spectrum is of interest for treatment studies for new treatment approaches for cigarette addictions.